Elity medyczne versus elity polityczne: kryzys elit zaufania publicznego - Gałuszka, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2009)
The article analyzes the crisis of political and medical elites in the context of honesty, reliability and diligence. The starting point is the notion of “professional elite” and the differences between representatives of both groups. The text emphasizes the public resonance and interpretation of both professions. According to E. Freidson’s theoretical model, the physician`s and politician`s authorities have different reasons, functions and legitimization. Both professions are based on public trust in interaction practices. The public expectations are focused mostly on instrumental and axiological trust. Obeying various rules and norms is expected from both professions but the social control and sanctions are different. Both physicians and politicians have their own ethical codes; the problem is that they are not always respected. The article concludes with discussion on the notion of risk in both professions and presents suggestions about what elites should do to maintain or regain public trust.